New information to Queretaro´s bird fauna, Mexico. - Pineda López, Rubén; Arellano Sanaphre, Alejandro; Almazán Núñez, R. Carlos; López González, Carlos; González García, Fernando (Instituto de Ecología, A.C., 2010)
We present new information about 24 species, including 12 noteworthy records for the avifauna of the Mexican state of Queretaro. These data were gathered during fieldwork performed between 1993 to 2007, mainly in the Eje Neovolcánico province. Five species are considered protected under Mexican law NOM-059-SEMARNAT-2001: Buteogallus anthracinus, Buteo albonotatus, Trogon collaris, Turdus infuscatus and Vermivora crissalis. The checklist of birds present in Queretaro is now at least 347 species.